Teacher Pedagogic Competency In Implementing Independent Learning Curriculum At Min 1 Medan - Mhd. Rizkiy Bahar Siregar; Rusydi Ananda; Mahariah Mahariah (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
. Pedagogical competence is an essential skill that a teacher must have to effectively oversee the learning process, which encompasses comprehending student characteristics, planning, executing, assessing learning, and fostering student potential. In the implementation of the Merdeka Curriculum at MIN 1 Medan, pedagogical competency is essential for the effective execution of innovative learning that addresses student needs. This study revealed that the pedagogical competency of Fiqh teachers at MIN 1 Medan necessitates enhancement, particularly regarding the integration of technology and the implementation of teaching methods that align with the Merdeka Curriculum. This research seeks to evaluate the level of pedagogical competency among Fiqh instructors and the challenges encountered in the implementation of the Merdeka Curriculum. We employ a qualitative research methodology, utilizing data collection approaches such as observation, interviews, and documentation. The research findings reveal persistent weaknesses in the proficiency of technology and creative pedagogical methods, which impede the enhancement of the teaching and learning process. Enhancing teachers' pedagogical competencies through training and technical support has emerged as a crucial proposal for the successful implementation of the Merdeka Curriculum at MIN 1 Medan.